History of vasomotor symptoms, extent of coronary artery disease, and clinical outcomes after acute coronary syndrome in postmenopausal women. Issue 6 (June 2018) - Ferri, Luca A.; Morici, Nuccia; Bassanelli, Giorgio; Franco, Nicoletta; Misuraca, Leonardo; Lenatti, Laura; Jacono, Emilia Lo; Leuzzi, Chiara; Corrada, Elena; Aranzulla, Tiziana C.; Colombo, Delia; Cagnacci, Angelo; et al.
Abstract: Objective: Vasomotor symptoms (VMS) during menopausal transition have been linked to a higher burden of cardiovascular risk factors, subclinical vascular disease, and subsequent vascular events. We aim to investigate the association of VMS with the extent of coronary disease and their prognostic role after an acute coronary syndrome. Methods: The Ladies Acute Coronary Syndrome study enrolled consecutive women with an acute coronary syndrome undergoing coronary angiography. A menopause questionnaire was administered during admission. Angiographic data underwent corelab analysis. Six out of 10 enrolling centers participated in 1-year follow-up. Outcome data included the composite endpoint of all-cause mortality, recurrent myocardial infarction, stroke, and rehospitalization for cardiovascular causes within 1 year. Results: Of the 415 women with available angiographic corelab analysis, 373 (90%) had complete 1-year follow-up. Among them, 202 women had had VMS during menopausal transition. These women had the same mean age at menopause as those without VMS (50 years in both groups), but were younger at presentation (median age 71 vs 76 years; P  < 0.001), despite a more favorable cardiovascular risk profile (chronic kidney dysfunction 4.5% vs 15.9%; P  = 0.001; prior cerebrovascular disease 4.5 vs 12.2%; P  = 0.018). Extent of coronary disease at angiography was similar between groups (mean Gensini score 49 vs 51; P  = 0.6; mean SYNTAX score 14 vs 16; P  = 0.3). Overall cardiovascular events at 1 year did not differ between groups (19% vs 22%; P  = 0.5). Conclusions: In postmenopausal women with an acute coronary syndrome, a history of VMS was associated with younger age at presentation, despite a lower vascular disease burden and similar angiographically defined coronary disease as compared with women without VMS. No difference could be found in terms of overall clinical outcomes. These results should be interpreted cautiously as all analyses were unadjusted and did not account for risk factor differences between women with and without a history of VMS.